A study on femtosecond laser in glaucoma treatment : energy deposition and thermal increase - Hou, Dongxia (2008)
In this thesis work, femtosecond laser-ocular tissue interaction was studied. A femtosecond laser-induced moving breakdown model was introduced to predict the optical breakdown threshold; a Heat Affected Zone model was used to analyze temperature increases. Furthermore, to investigate light propagation in multilayered ocular tissue, a Monte Carlo program was developed. The transmission, reflection and absorption of the light were statistically calculated. Key laser parameters and their effects on the ablation process in the ocular tissue were studied. To reduce the cost of the laser surgery setup and minimize certain intra tissue damage, nano Joule pulse processing in ocular tissues was studied using a femtosecond oscillator. Both the simulation and in-vitro experimentation results achieved in this research provide valuable information for femtosecond laser application in glaucoma treatment.